The mobile context framework: providing context to mobile applications - Oliveira, Luís Filipe Silva de (2013)
The spread of mobile devices in modern societies has forced the industry to create software paradigms to meet the new challenges it faces. Some of these challenges are the huge heterogeneity of devices or the quick changes of users’ context. In this scenario, context becomes a key element, enabling mobile applications to be user centric and adapt to user requirements. The Mobile Context Framework, proposed in this paper, is a contribution to solve some of these challenges. Using Web servers running on the devices, context data can be provided to web applications. Besides the framework’s architecture, a prototype is presented as proof of concept of the platform’s potential.